2018
DOI: 10.3126/jfl.v16i1.22881
|View full text |Cite
|
Sign up to set email alerts
|

REDD+ and Community Forestry in Nepal: Strengthening or Paralysing Decentralised Governance?

Abstract: At a time when community forestry has become a prominent mode of forest governance in many developing countries, REDD+ (Reducing Emissions from Deforestation and Forest degradation) has emerged as a new conservation policy to contribute to climate change mitigation by incentivising such countries to conserve forest. While the proponents of REDD+ claim that it can help to strengthen decentralised forest governance through an increased flow of resources of fund and knowledge, the critics evince that there are ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The trend of decentralization can be reversed as REDD+ monitoring technical complexity required more centralized governance. (Khatri, Maskey, et al, 2018),in their study also claimed that although CF has strengthened due to increased income source, REDD+ interventions can weaken decentralization of CF by giving limited rights in the CFUGs' decisions. Also, REDD+ funding mechanism may incite the governments to reverse the trend of decentralization towards a centralized forest governance system for the purpose of reaping rewards more centrally (Sandbrook et al, 2010).Analysis also showed that REDD+ policies have been developed and interventions are made in a way local people's participation and representation of their voices is limited which may weaken and reverse the trend of forest decentralization (Bushley and Khatri, 2011;Ojha et al, 2013;.…”
Section: Redd+ and Cf Governancementioning
confidence: 95%
See 3 more Smart Citations
“…The trend of decentralization can be reversed as REDD+ monitoring technical complexity required more centralized governance. (Khatri, Maskey, et al, 2018),in their study also claimed that although CF has strengthened due to increased income source, REDD+ interventions can weaken decentralization of CF by giving limited rights in the CFUGs' decisions. Also, REDD+ funding mechanism may incite the governments to reverse the trend of decentralization towards a centralized forest governance system for the purpose of reaping rewards more centrally (Sandbrook et al, 2010).Analysis also showed that REDD+ policies have been developed and interventions are made in a way local people's participation and representation of their voices is limited which may weaken and reverse the trend of forest decentralization (Bushley and Khatri, 2011;Ojha et al, 2013;.…”
Section: Redd+ and Cf Governancementioning
confidence: 95%
“…For deprived and medium-class users revenue generating activities were executed in both Kankali CFUG and Janapragati CFUG. In CFUGs, the disadvantaged group's representation in the executive committee has improved, though they feel that their voices do not impact the decision on CFUG and benefit sharing (Devkota, 2019).According to (Khatri, Maskey, et al, 2018), the REDD+ pilot project mandate the CFUGs to spent at least 50% of carbon payment funds in poverty minimization and livelihood upliftment activities targeting disadvantage groups, as these activities were included in the Forest Carbon Trust Fund (FCTF) Operational Guidelines. Additionally, CFUGs has practiced various climate change adaptation measures to cope with climate change (Godar Chhetri, 2012).…”
Section: The Implication Of Redd+ On Cf Governance In Nepalmentioning
confidence: 99%
See 2 more Smart Citations
“…Nepal's forest policy and legislation has lingering uncertainty about forest tenure and allocation of rights of access and control. For example, in the region of the Terai, demands by distant users is often a justification for denying local community rights (Khatri et al, 2018 get other indirect benefits. A unique arrangement in this case was to differentiate people living in areas close to the project site and other "affected areas" outside and to provide benefits on that basis.…”
Section: Distribution Issuesmentioning
confidence: 99%